Evolution of Educational Administration in Chile and Professionalizing School Administration in 2020 - Yeomans Cabrera, María Mercedes (2021)
As is in many other countries, educational administration in Chile has adapted to the emerging needs of the country. In 2020, a new public school educational system was gradually implemented, thereby, ending the municipal educational model established 40 years before by the military government. School administration has become more complex given the rise in schoolwide coverage. The objective of this study is to describe events that led to the current administration model using a timeline of policies pertaining to the educational system and the evolution of a professional career path for public school principals. This study is based on qualitative research using a descriptive approach based on a literature review. Public school administration efforts initially focused on school coverage and afterwards on improving the quality of education. The last few decades were characterized by educational reforms and paradigm innovations with an emphasis on school inclusion with a focus on non-profit education. Becoming a principal in the Chilean public school system is not an easy feat. Currently, Chile is considered to be one of the countries with the highest demands in accessing this position since it is based on merit with oversight based on the Law of Transparency. It is concluded that the rigorous nature of Chile´s public educational administrative system should also extend to the private school system to ensure that administrative decisions will, most likely, be based on academic criteria and respect for each institution´s educational goals.